THE SILENT SCREAM OF THE REEF: VISUALISING CORAL BLEACHING IN CHASING CORAL - Devan , Gayathri J; M G Priya (International Journal of Research -GRANTHAALAYAH, 2025)
Chasing Coral, a 2017 documentary film, captures the much-overlooked ecological issue of coral bleaching. The film perfectly encapsulates the devastation of the coral ecosystem that is a reflection of the global climate change which will soon become irreversible if left unattended immediately. This paper aims to tease out the harmful effects of Sargassum Algae and the rising temperature at sea that are directly responsible for the destruction of the coral ecosystems. The theoretical framework of Ecological Film Studies and Environmental Visual Rhetoric is employed to explore the complex scientific records of climate data and to relate it in a comprehensible literary and humanitarian perspective. The powerful environmental call to action will be conveyed through an in-depth analysis of the narration of the documentary that describes the hard work and the findings of the team of scientists and divers who are tracking the phenomenon of bleaching among the coral reefs. The documentary serves as a critical means towards climate crusading and a study of such an environmental film will help bridge the gulf between scientific vision and public awakening, inspiring ecological awareness in the wake of climate crisis.